“Spontaneous” CSF Fistula due to Transtegmental Brain Herniation in Combination with Signs of Increased Intracranial Pressure and Petrous Bone Hyperpneumatization: An Illustrative Case Report - Rivera, Diones; Fermin-Delgado, Rafael; Stoeter, Peter (Journal of Neurological Surgery Reports, 2014)
Background and Importance Transtegmental brain herniation into the petrous bone is a rare cause of rhinoliquorrhea. Our case presents a combination of several typical clinical and imaging findings illustrating the ongoing etiologic discussion of such cerebrospinal fluid (CSF) fistulas.Clinical Presentation A 53-year-old man presented with nasal discharge after a strong effort to suppress coughing. Imaging revealed a transtegmental herniation of parts of the inferior temporal gyrus into the petrous bone and in addition a combination of signs of chronically increased intracranial pressure and a hyperpneumatization of the petrous bone. The fistula was closed by a middle cranial fossa approach.Conclusion The case illustrates the two main predisposing factors for development of petrous bone CSF fistulas: increased intracranial pressure and thinning of the tegmental roof due to extensive development of air cells. Because the CSF leakage repair does not change the underlying cause, patients have to be informed about the possibility of developing increased intracranial pressure and recurrences of brain herniations at other sites.
Keywords: CSF fistula; brain herniation; increased intracranial pressure; petrous bone